Pengaruh Sumber Daya Alam Terhadap Pertumbuhan Ekonomi Di Kabupaten Tanjung Jabung Timur - Rezky Maulana Akbar; Agustina Mutia; Fauzan Ramli (Institut Nalanda, 2024)
Natural resources are a major contributor to the formation of the national and domestic gross product, serving as a primary source of employment and being one of the dominant sectors in generating community income. Natural resources play a crucial role as supporting factors for economic growth in Tanjung Jabung Timur Regency. Despite consistently making significant contributions to the Regional Gross Domestic Product (PDRB) from 2013 to 2022, the economic growth rate of the Natural Resources Sector in Tanjung Jabung Timur tends to be slow. This research aims to investigate the influence of natural resources on economic growth in Tanjung Jabung Timur during the period 2013-2022. The study uses purposive sampling for its sample selection. The data utilized comprises time series data from 2013 to 2022. The results of this research indicate that variable X does not have a significant impact on variable Y at the 0.05 significance level. Therefore, the null hypothesis stating that there is no significant influence from variable X1 (Sector A) and X2 (Sector B) on variable Y (Growth Rate) is accepted. The statistical test results show that the p-value for variable X is greater than the predetermined significance level (p > 0.05). This indicates the insignificance of the relationship between variable X and variable Y. In other words, the variation in variable X cannot significantly explain the variation in variable Y in the context of this study.